The complete mitochondrial genome of Amorphophallus albus and development of molecular markers for five Amorphophallus species based on mitochondrial DNA - Shan, Yuanyu; Li, Jingling; Zhang, Xue; Yu, Jie (Frontiers in Plant Science, 2023)
Amorphophallus albus is an herbaceous, cormous, perennial plant used as a food source and traditional medicine in Asia. In this study, we assembled and annotated the complete mitochondrial genome (mitogenome) of A. albus, which consists of 19 circular chromosomes.The total length of A. albus mitogenome is 537,044 bp, with the longest chromosome measuring 56,458 bp and the shortest measuring 12,040 bp. The overall GC content of A. albus mitogenome is 46.19%. We identified and annotated a total of 36 protein-coding genes (PCGs), 21 tRNA genes, and 3 rRNA genes in the mitogenome. Analysis of repeated elements revealed the presence of 126 SSRs and 518 pairs of dispersed repeats in A. albus mitogenome.Additionally, we analyzed mitochondrial plastid DNAs (MTPTs) and identified 20 MTPTs between the two organelle genomes, with a combined length of 22,421 bp, accounting for 12.76% of the plastome. Besides, we predicted a total of 676 C to U RNA editing sites on 36 protein-coding genes of high confidence using Deepred-mt. Furthermore, extensive genomic rearrangement was observed between A. albus and the related mitogenomes. We conducted phylogenetic analyses based on mitochondrial PCGs to determine the evolutionary relationships between A. albus and other angiosperms. Finally, we developed and validated two molecular markers, Ai156 and Ai976, based on two intron regions (nad2i156 and nad4i976) respectively. The discrimination success rate was 100 % in validation experiments for five widely grown konjac species. Our results reveal the multi-chromosome mitogenome of A. albus, and the developed markers will facilitate molecular identification of this genus.